Plant Small RNA World Growing Bigger: tRNA-Derived Fragments, Longstanding Players in Regulatory Processes - Alves, Cristiane S.; Nogueira, Fabio T. S. (Frontiers in Molecular Biosciences, 2021)
In the past 2 decades, the discovery of a new class of small RNAs, known as tRNA-derived fragments (tRFs), shed light on a new layer of regulation implicated in many biological processes. tRFs originate from mature tRNAs and are classified according to the tRNA regions that they derive from, namely 3′tRF, 5′tRF, and tRF-halves. Additionally, another tRF subgroup deriving from tRNA precursors has been reported, the 3′U tRFs. tRF length ranges from 17 to 26 nt for the 3′and 5′tRFs, and from 30 to 40 nt for tRF-halves. tRF biogenesis is still not yet elucidated, although there is strong evidence that Dicer (and DICER-LIKE) proteins, as well as other RNases such as Angiogenin in mammal and RNS proteins family in plants, are responsible for processing specific tRFs. In plants, the abundance of those molecules varies among tissues, developmental stages, and environmental conditions. More recently, several studies have contributed to elucidate the role that these intriguing molecules may play in all organisms. Among the recent discoveries, tRFs were found to be involved in distinctive regulatory layers, such as transcription and translation regulation, RNA degradation, ribosome biogenesis, stress response, regulatory signaling in plant nodulation, and genome protection against transposable elements. Although tRF biology is still poorly understood, the field has blossomed in the past few years, and this review summarizes the most recent developments in the tRF field in plants.